Faktor-faktor yang Mempengaruhi Belum Maksimalnya Pelaksanaan Hasil Diklat Eksternal Rumah Sakit Universitas Muhammadiyah Malang - Nuthea, Merry (Jurnal Ilmiah Administrasi Publik, 2018)
One of the programs needed to evaluate the success of a training is training evaluation. According to the data from the education and training department of the studied hospital, the implementation of training result was still lacking. The objectiove of this study was to find out the factors contributing to the lack of implementation of the result of external training in Muhammadiyah University Hospital Malang. The method used in this study was observation, document review, and interview. The result showed that the knowledge which the staffs got from the external training was not implemented properly. From ten external trainings observed, about 30% of them was not implemented properly. Fishbone diagram showed that the main factor was there was no post-training evaluation. The solution was to make a guideline and standard operating procedure regarding post-training evaluaiton.